Physical and phonological causes of coda /t/ glottalization in the mainstream American English of central Ohio. Issue 1 (30th December 2020) - Seyfarth, Scott; Garellek, Marc
In American English, a glottal stop is sometimes pronounced in place of an expected syllable coda /t/, and audible glottalization is attested before both /t/ and /p/ in coda position. Following previous work, we claim that the voiceless stops in American English involve a glottal constriction gesture to produce voicelessness in coda position, which contrasts with the glottal spreading gesture used in onset position. If the oral stop closure is not audibly produced, or if the oral and glottal gestures are not aligned, the resulting articulation may be perceived as a glottal stop or as pre-glottalized. This study explores the pre-consonantal phonological environments where coda glottal stops occur in a large corpus of American English speech from central Ohio. Coda /t/ glottalization is found near-categorically before sonorants, often phrase-medially before labial and velar obstruents, often phrase-finally, and occasionally elsewhere. We argue that most of this distribution can be explained by phonetic conditions which either favor reduction of the oral closure, or else reinforce the irregular voicing associated with the glottal constriction gesture. However, the near-categorical rate of glottalization before sonorants, as well as somewhat higher rates for younger and female speakers, may not have a plausible coarticulatory source: These suggest that the process is also phonologically planned under some circumstances.